2005
DOI: 10.1159/000085207
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in Somatoform Pain Disorder: Sleep Laboratory Studies on Differences to Controls and Acute Effects of Trazodone, Evaluated by the Somnolyzer 24 × 7 and the Siesta Database

Abstract: Patients with chronic pain often suffer from sleep disturbances, specifically decreased deep sleep, and thus may get into a vicious circle which maintains their pain condition. Utilizing polysomnography and psychometry, objective and subjective sleep and awakening quality was investigated in 11 patients with nonorganic insomnia (F51.0) related to somatoform pain disorder (SPD; F45.4) as compared with age- and sex-matched healthy controls of the Siesta normative database. Patients demonstrated a markedly deteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 122 publications
2
16
0
Order By: Relevance
“…Saletu et al [43] found reduced sleep efficiency and sleep fragmentation (increased arousal index) in patients with somatoform pain disorder, which is similar to our findings in patients with SD.…”
Section: Polysomnographic Findingssupporting
confidence: 91%
“…Saletu et al [43] found reduced sleep efficiency and sleep fragmentation (increased arousal index) in patients with somatoform pain disorder, which is similar to our findings in patients with SD.…”
Section: Polysomnographic Findingssupporting
confidence: 91%
“…7 to a pharmaco-sleep study in normals [56] and an example of a clinical study using the Somnolyzer 24 ! 7 [57] can be found in the present issue of Neuropsychobiology .…”
Section: Discussionmentioning
confidence: 95%
“…This study was acknowledged as 1 of only 2 evidence level 1 studies for sleep classification according to R&K by the Digital Task Force Committee of the American Academy of Sleep Medicine (AASM) [13] . First applications of the Somnolyzer in a double-blind, placebo-controlled pharmaco-sleep study on the potential interaction of 20 mg paroxetine and 1 mg alprazolam in healthy young volunteers and in a single-blind, placebo-controlled clinical sleep study on the acute effects of 100 mg trazodone in patients with nonorganic insomnia related to somatoform pain disorder confirmed the validity of the classifier for scoring PSGs after treatment with psychotropic drugs [14,15] . This validity was further confirmed by Svetnik et al [16] in 164 PSGs of 82 subjects in a clinical trial using zolpidem in a phase advance model of transient insomnia.…”
Section: Introductionmentioning
confidence: 81%